Manajemen Strategi Segmenting, Targeting, Positioning dalam Pemasaran Internasional - Masbullah Masbullah; Salmi Yuniar Bahri (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
In general, to increase the sales of products or services offered, companies need to carry out marketing activities. Amid the increasingly intense business competition, each company must establish the right policies to achieve their goals and desires. Therefore, the right strategic analysis is necessary, one of which is the application of the STP strategy (Segmenting, Targeting, Positioning). This research uses the Library Resources method, which focuses on gathering data from literature studies. In international marketing, segmentation strategy is carried out by determining the segment size, developing the segment, analyzing the costs of using the segment, ensuring alignment, and assessing competitive positioning. Meanwhile, targeting strategy involves approaches such as focusing on a single market, product specialization, selective specialization, and total coverage. For positioning strategy, the steps include identifying competitive advantages, creating those advantages, and evaluating the reactions of the target.